THE CORRELATION BETWEEN STUDENTS’ ONLINE LEARNING READINESS AND THEIR ENGLISH LEARNING ACHIEVEMENT - Zikriyah Zikriyah; Nurdin Noni; Maemuna Muhayyang (Universitas Negeri Makassar, 2022)
This research aims to determine the students’ level of online learning readiness, their English learning achievement, and to describe whether there is a significant correlation between those two variables. The population of this research was the students of English Education 2019, Faculty of Languages and Literature, Universitas Negeri Makassar with a total of 148 students and taking 37 students as a sample using purposive sampling. The design of this research is quantitative correlational research. The data were collected using the OLRS questionnaire (developed by Hung et al. (2010)) with a Likert model scale. Analysis of the data in this research was using the SPSS 25 program. The results of this research indicate that: (1) The students’ level of online learning readiness was in